Free Fatty Acid Receptor G-protein–coupled Receptor 40 Mediates Lipid Emulsion-induced Cardioprotection. (July 2018) - Umar, Soban; Li, Jingyuan; Hannabass, Kyle; Vaillancourt, Mylene; Cunningham, Christine M.; Moazeni, Shayan; Mahajan, Aman; Eghbali, Mansoureh
Abstract : Background: We have previously shown that intralipid (lipid emulsion) protects the heart against ischemia/reperfusion injury and bupivacaine-induced cardiotoxicity. However, the precise underlying mechanisms are not fully understood. Here we explored the hypothesis that free fatty acid receptor-1 or G-protein–coupled receptor 40 is expressed in the heart and that cardioprotective effects of lipid emulsion are mediated through G-protein–coupled receptor 40 in two animal models of ischemia/reperfusion injury and bupivacaine-induced cardiotoxicity. Methods: Langendorff-perfused male mouse hearts were subjected to ischemia/reperfusion with lipid emulsion alone (1%) or with G-protein–coupled receptor 40 antagonist (GW1100, 10 µM). Additionally, cardiotoxicity was achieved in male rats with bupivacaine bolus (10 mg/kg, IV) followed by lipid emulsion alone (20%, 5 ml/kg bolus, and 0.5 ml · kg –1 · min –1 maintenance, IV) or with GW1100 pretreatment (2.5 mg/kg, IV). Results: G-protein–coupled receptor 40 is expressed in rodent hearts. GW1100 abolished lipid emulsion-induced cardioprotection against ischemia/reperfusion in mice because rate pressure product and left ventricular developed pressure were lower than lipid emulsion alone (rate pressure product: 2, 186 ± 1, 783 [n = 7] vs. 11, 607 ± 4, 347 [n = 8]; left ventricular developed pressure: 22.6 ± 10.4 vs. 63.8 ± 20; P < 0.0001). Lipid emulsion + GW1100 also demonstrated reduced LV dP/dtmax and LV dP/dtmin (dP/dtmax = 749 ± 386 vs. 2, 098 ± 792, P < 0.001; dP/dtmin = −443 ± 262 vs. −1, 447 ± 546, P < 0.001). In bupivacaine-induced cardiotoxicity rat model, GW1100 pretreatment had no significant effect on heart rate (HR) and ejection fraction after 30 min (HR: 302 ± 17 vs. 312 ± 38; ejection fraction: 69 ± 3% vs. 73 ± 4%). GW1100 pretreatment, however, prevented lipid-rescue, with no recovery after 10 min. In the control group, lipid emulsion improved HR (215 ± 16 at 10 min) and fully rescued left ventricle function at 10 min (ejection fraction = 67 ± 8%, fractional shortening = 38 ± 6%). Conclusions: G-protein–coupled receptor 40 is expressed in the rodent heart and is involved in cardioprotection mediated by lipid emulsion against ischemia/reperfusion injury and bupivacaine-induced cardiotoxicity. Abstract : This study demonstrates that G-protein–coupled receptor 40 is expressed in the rodent heart and is involved in cardioprotection mediated by lipid emulsion against ischemia/reperfusion injury and bupivacaine-induced cardiotoxicity.